Polymerized Urushiol of the Commercially Available Rhus Product in Korea - Cheong, Seung Hyun (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2010)
BACKGROUND: Systemic contact dermatitis commonly occurs with the intake of rhus (boiled chicken with rhus) as a health food and a folk medicine to cure gastrointestinal diseases in Korea. Rhus companies insist they have the technology for rhus detoxification. However, the numbers of systemic allergic contact dermatitis patients, caused by rhus, have not decreased. The principle of present techniques for rhus detoxification is the induction of the polymerization of urushiol, but polymerized urushiol may still have antigenicity, although to a diminished degree. The Korean Food and Drug Administration (KFDA) has a regulation to control urushiol use as a food. However, the laboratory method that KFDA uses for detection of rhus can only detect the urushiol monomer. OBJECTIVE: We conducted experiments to detect polymerized urushiol in rhus products, which were considered not to include urushiol by the KFDA. METHODS: Rhus product approved by the KFDA was separated with chloroform. The chloroform fractionation was accomplished on a recycle HPLC system. Four peaks were achieved and evaporated to give an amorphous powder. Each powder was analyzed on a NMR system and mass spectrometer. RESULTS: The material considered to be urushiol dimer, with a 638 molecular weight (MW), was detected in one of the four powders as per the HPLC peaks. CONCLUSION: We concluded that commercially available rhus product is comprised of material considered to be urushiol dimer. Therefore, even if the antigenicity of the rhus products is low, this product may cause adverse effects and is not completely detoxified.